ANALISIS ASUHAN KEPERAWATAN PADA PASIEN MULTIPLE FRAKTUR EKSTREMITAS BAWAH DENGAN PENERAPAN ELEVASI KAKI 20° TERHADAP PENINGKATAN PERFUSI PERIFER - Maila Faiqoh Tsauroh (2023)
Open reduction and internal fixation (ORIF) is a medical treatment for extremity bone fractures that consists of surgical methods paired with internal fixation. However, this can cause complications such as pain and swelling in the operated body part. One of the nursing intervention to increase in peripheral perfusion is by elevating the lower extremities by 20°. This study was conducted to determine the effectiveness of elevating the lower extremities by 20° in improve peripheral perfusion in patients post-lower extremity fracture surgery. This study used a case study method with a nursing care approach by taking two cases as the unit of analysis. The unit of analysis was patients with Post ORIF Multiple Lower Extremity Fractures in one of the hospitals in Jakarta. The results on the fifth day showed a decrease in pain from a scale of 6 to 2 and a decrease in swelling in the left ankle circumference on the third day from 28.3 cm to 26.7 cm on the fifth day. The 20° elevation technique of the lower extremities accompanied by a dorsoplantar movement combination is recommended for patients with post-ORIF lower extremity fractures to increase in peripheral perfusion.